Effects of zinc oxide nanoparticles on human coronary artery endothelial cells. (July 2016) - Chuang, Kai-Jen; Lee, Kang-Yun; Pan, Chih-Hong; Lai, Ching-Huang; Lin, Lian-Yu; Ho, Shu-Chuan; Ho, Kin-Fai; Chuang, Hsiao-Chi
Abstract: Inhalation of zinc oxide (ZnO) metal fumes is known to cause metal fume fever and to have systemic effects; however, the effects of ZnO nanoparticles (ZnONPs) on the cardiovascular system remain unclear. The objective of this study was to investigate the cardiovascular toxicity of ZnONPs. Human coronary artery endothelial cells (HCAECs) were exposed to ZnONPs of different sizes to investigate the cell viability, 8-hydroxy-2'-deoxyguanosine (8-OHdG), interleukin (IL)-6, nitric oxide (NO), and regulation of cardiovascular disease-related genes. Exposure of HCAECs to ZnONPs resulted in decreased cell viability and increased levels of 8-OHdG, IL-6, and NO. Downregulation of cardiovascular-associated genes was observed in response to ZnONPs in HCAECs determined by qPCR, suggesting that the calcium signaling pathway, neuroactive ligand-receptor interaction, hypertrophic cardiomyopathy, dilated cardiomyopathy, and renin-angiotensin system are important affected pathways in response to ZnONPs. Furthermore, we observed a significant response of AGTR1 to ZnONP exposure in HCAECs. Our results suggest that ZnONPs cause toxicity to HCAECs, which could be associated with cardiovascular dysfunction. Highlights: Effects of ZnONP were determined in HCEAC. Alteration in 8-OHdG, IL-6 and NO occurred by ZnONPs. AGTR1 is an important gene in response to ZnONP exposure. Calcium signalling pathway is important after ZnONPs exposure. ZnONP is associated with coronary artery endothelial cell dysfunction.